Sleep Quality and Academic Performance of Upper Basic Education Students in Social Studies in Cross River State, Nigeria - Edinyang, S. D.; Effiom, Veronica Nakanda; Effiom, John Edwin; Ushie, Doris; Adams, Amina Odugbo (Richtmann Publishing, 2020)
This paper analyzed sleep quality and academic performance of Upper Basic Education (UBE) students in Social Studies. One research question and statement of hypothesis were formulated to guide the study. The literature review was done dependent on the variable under examination. The survey research design was used in the study. The outcome of the research uncovered that there is an impact of sleep quality on the academic performance of students in social studies.